The Cornfield’s Monster Diva: CeWEBrity Leslie Hall Takes Midwest Stereotypes to Camp - LaPorte, Kait (My University, 2018)
This dissertation analyzes the music videos and persona of internet celebrity Leslie Hall. I demonstrate how the widely circulated narrative that any ordinary person can become famous on YouTube created the ideal setting for Hall’s Midwest shtick to attain fame. Further, I show how Hall campily and deliberately embodies Midwestern stereotypes in order to make fun of the representations of the region as an historic, forgotten one. Building on that, I assert that Hall queers the Midwest by juxtaposing the tacky and the ordinary, giving voice to Midwestern queerness and pushing back against the Hollywood glamour of mainstream gay iconicity. Building on my discussion of the ways in which Hall queers the Midwest and pushes against the region’s alleged heteronormativity, I explore how Hall’s work reveals the relationship between fatness and monstrosity in American society, and utilizes this association in order to call attention to it. In so doing, Hall paints a new picture of the Midwest in which it is queer, famous, and monstrous.
Thesis (Ph.D.)--University of Washington, 2018
Keywords: Fat studies; Midwest; Monstrosity; Music video; Rural queerness; YouTube; Music; Gender studies; Regional studies; Music